(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
This cross-sectional study was conducted to compare lipid profile status in hypothyroid patients attending at indoor and outpatient Department (OPD) of Medicine and Endocrinology, Sir Salimullah Medical College & Mitford Hospital, Dhaka over a period 6 months from March to September 2008. A total of 80 patients (of which 30 patients formed the control group) aged 12 to 60 years, not taking thyroxin in the last 3 months and not taking lipid lowering agents were included in the study. Patients with secondary hypothyroidism, chronic renal failure, liver diseases, pregnancy, dyslipedamia (with or without lipid lowering agents) were excluded from the study. Data collected on variables of interest were analyzed using Chi-squared (c2) or Fisher`s Exact Probability tests, Student’s t-test and person correlation co-efficient test was done to see the correlation of lipid profile with the severity of hypothyroidism. The mean value of TSH, total cholesterol, low-density lipoprotein cholesterol (LDL-C) and triglyceride in case group were significantly higher than those in control group but the mean high density lipoprotein cholesterol (HDL-C) was lower in case group compared to control group. The findings of the study indicate that THS shows positive correlation with total cholesterol, LDL cholesterol and triglyceride (r = 0.025, p = 0.865, r = 0.258, p = 0.071 and r = 0.078, p = 0.589 respectively) and HDL cholesterol exhibiting a negative correlation (r = -0.055, p = 0.704). These results confirm that thyroid dysfunction is common, and may be associated with adverse health outcomes. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 4-8